Escándalo y locura en la élite chilena: el asesinato de Teresa Zañartu, 1905 - Jeniffer Cerón Sandoval (Centre de Recherches sur les Mondes Américains, 2018)
In 1905, inside the Municipal Theater of Santiago de Chile, Eduardo Undurraga murdered his ex-wife, Teresa Zañartu. Years of marriage problems resulting in their subsequent divorce led to a transgression to the social order that could not be contained within their family, thus culminating in a crime perpetrated before the eyes of Santiago’s elite. Through the study of this case, this text analyzes the crossings of scandals from the private sphere into public space. The relevance of the case activates diverse mechanisms for scandal administration, such as the guarding of family’s intimacy from the public knowledge, publications in the press, and access to formal justice, all while trying to claim the honor and reputation of Zañartu and Undurraga. Finally, the analysis of this case allows us to understand the forms of vindication of the public image of the Santiago elite’s because the murder put in check the values promoted by them at the beginning of 20th century.